Towards a reorganisation system for sovereign debt : an international law perspective - Schier, Holger (Martinus Nijhoff Publishers, 2007)
The insolvency of sovereign debtors is a virtually timeless phenomenon and yet the existing international financial architecture does not provide any legal framework to deal with this issue. Following an overview of the main proposals as to how to bridge this gap, this study analyses the extent to which public international law can be used as a source for the establishment of a reorganisation system for sovereign debt. While there is no adequate customary international law relating to sovereign insolvencies, reference can instead be made to the growing body of general principles of law. This i.